Lack of Awareness of HPV Vaccination Contributing to the Low Uptake of the Vaccination amongst Young HIV Negative Women in Western Kenya – A Case Study of Jaramogi Oginga Odinga Teaching and Referral Hospital - Ajwang, Arthur; Ogutu, George; Khama, Rogo; Otoi, Shem; Estambale, Benson (Science Set Journal of Cancer Research, 2024)
Human papilloma virus (HPV) is the leading cause of ano-genital cancers globally with cervical cancer as the top cause of cancer-related deaths in women and over 90% of these deaths occur in low- and middle-income countries. HPV Vaccination provides protection against HPV types 16 and 18 which are responsible for 70% of cervical cancer cases. This study aimed at examining the awareness of HPV Vaccination amongst young HIV Negative women with early onset cancer of the cervix presenting at the Oncology Clinic of the hospital. A mixed method study was undertaken of purposively recruited HIV negative patients, aged 13-35 years, presenting with early onset Cancer of the Cervix in the 2020-2021 period of study. The study found out that, in the period 2020-2021, there were 0% awareness of HPV Vaccination and 0% uptake of the vaccination amongst HIV negative young women, aged 13-35 years old, with early onset cancer of the cervix. Our conclusion is that there is lack of awareness of HPV and hence no uptake of the vaccination amongst the young women in Western Kenya, and this may be contributing to low vaccine uptake in this region.
Keywords: Human Papilloma Virus; Vaccination; Awareness; low Uptake; Early Onset; Young-Women; HIV Negative; Western Kenya